ROLE OF THE RUSSIAN FEDERATION IN THE ENERGY SECURITY OF THE BRICS COUNTRIES - E. Shilets; A. Boiko; O. Klochkova (Вестник Северо-Кавказского федерального университета, 2022)
As a result of the research, scientific and practical recommendations on the formation of energy security of the Russian Federation and its role in enhancing the energy security of the BRICS countries have been developed. It is substantiated that the formation of energy security of the BRICS countries is closely interconnected with the economic development of the countries and their mutually beneficial cooperation in the field of energy. It is established that the strengthening of the energy security of the BRICS countries is influenced by the strengthening of political, economic and trade aspects of the partnership between the Russian Federation and the BRICS countries in the conditions of volatility of the external and internal environment. The article proposes directions for increasing the efficiency of energy security of BRICS countries.